Knowledge, Attitudes, and Practices of Pediatric Long-term Care Facility Staff Regarding Infection Control for Acute Respiratory Infections and Influenza Vaccination. (18th December 2019) - Saiman, Lisa; Wilmont, Sibyl; Hill-Ricciuti, Alexandra; Jain, Meaghan; Collins, Emily; Ton, Adrienne; Neu, Natalie; Prill, Mila M; Garg, Shikha; Larson, Elaine; Stone, Nimalie D; Gerber, Susan I; et al.
Abstract: We surveyed clinical staff and on-site teachers working at pediatric long-term care facilities regarding prevention and control of acute respiratory infections and influenza in staff and residents. We uncovered knowledge gaps, particularly among teachers and clinical staff working <5 years at sites, thereby elucidating areas for targeted staff education.